Factors Influencing Non-Performing Financing in Local and Foreign Islamic Banks in Malaysia: The Impact of Staff Efficiency as a Moderator - M. Rizki Fadillah; Maftukhatusolikhah; Rinol Sumantri; Maya Panorama; Peny Cahaya Azwari (LP2M IAIN Palopo, 2026)
The high level of Non-Performing Financing (NPF) in Malaysian Islamic banks, particularly higher fluctuations in foreign banks compared to local banks during 2017-2023, threatens financial stability with a market share of 40 percent. This study aims to analyze the influence of internal factors (ROA, FDR, FLP) and external factors (UR, IR, COC) on NPF, with staff efficiency as a moderator. Using a quantitative approach with panel data regression (Fixed Effect Model) and hierarchical regression, secondary data from Fitch Connect, Department of Statistics Malaysia, and Worldwide Governance Indicators. The population includes 16 Islamic banks (11 local, 5 foreign), a purposive saturated sample yielding 112 observations (77 local, 35 foreign). The results show that all six factors significantly affect NPF in local banks, while five factors in foreign banks; staff efficiency moderates FDR, FLP, IR for local and ROA, FLP, UR, IR, COC for foreign banks, improving risk mitigation. The conclusion recommends investment in staff training and anti-corruption policies to reduce NPF.